New records of amazonian Myrtaceae in Colombia - Carlos Parra-O; Edwin Trujillo Trujillo; Leslie Landrum (Caldasia)
Two new records of Myrtaceae (Myrcia ishoaquinicca and Psidium acidum) for the Amazonian forests of Caquetá, Cauca, and Putumayo departments, Colombia, are reported. Comments about the habitats in which these species are growing, as well as observations on their expanded distribution ranges, are included.